Korelasi Persepsi Orang Tua Terhadap Pendidikan Seks Pada Anak Usia Dini di Desa Nunu Utara Kecamatan Rainis Kabupaten Kepulauan Talaud - Suprianto Sasea; Meity N. Tanor; Nova L. I. M. Ogi (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2023)
The research problem in this study is the examination of the correlation between parental perceptions of sex education in early childhood in North Nunu Village, Rainis District, Talaud Islands Regency. The objective of this study is to establish the relationship between parental perspectives on sex education for young children in North Nunu Village, Rainis District, Talaud Islands Regency. A study was conducted in September to determine parents' attitudes of sex education in early childhood. The study employed a descriptive survey research method, utilising a quantitative methodology. According to the percentage calculations from the distributed questionnaire, it is evident that a significant number of parents expressed agreement rather than providing alternative answers when asked about their understanding of sex education for early childhood. Under the category of disagreement. The computation of the proportion for each indicator item has yielded a cumulative value of 1447, with an average of 72.35% indicating their agreement to receive instruction during early life. The correlation data computations indicate a positive association between parents' impressions of sex education in early infancy. Specifically, the resulting correlation coefficient (rxy) is 0.1000, based on data from 20 respondents. The significance level for this relationship is 0.05, and the critical value (rtable) is 0.422. These computations indicate that the value of rcount is greater than the value of rtable, with a significance level of 0.05. If the count of r is more than the count of rtable, then the hypothesis test concludes that there is a correlation between parents' judgements of sex education in early infancy.